2018
DOI: 10.3389/fpls.2018.00669
|View full text |Cite
|
Sign up to set email alerts
|

A Novel LncRNA, MuLnc1, Associated With Environmental Stress in Mulberry (Morus multicaulis)

Abstract: Environmental stresses are major constraints that limit the leaf productivity and quality of mulberry. LncRNAs have emerged as important regulators in response to biotic and abiotic stresses in plants. However, the functions and mechanisms of most lncRNAs remain largely unknown. A novel lncRNA designated as MuLnc1 was found to be cleaved by mul-miR3954 and produce secondary siRNAs in a 21 nt phase in mulberry. It was demonstrated that one of the siRNAs produced, si161579, can silence the expression of the calm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 65 publications
0
36
0
Order By: Relevance
“…Compared with the previously reported methods which mainly referred to physically filling the dynamic nanopores or chemically bonding to the hydroxyl groups, the strategy proposed in this study is a dual modification method, that is, the use of maleic anhydride (MAn) to improve wood durability (i.e., dimensional stability and decay resistance) via dynamic nanopore filling combined with hydroxyl group elimination. Although acetic anhydride, melamine formaldehyde, sorbitol, and N-methylol melamine have been reported to modify the cell wall for durability improvement in a similar strategy to our work, several drawbacks like the strong acid catalysts employed or formaldehyde release adversely affect their properties and the environment, and thus limit their practical applications [39][40][41][42][43]. Although maleic anhydride was reported to bulk the cell wall and chemically bond to the hydroxyl group, the employed methods still use solvents like DMSO, which are difficult to remove after the reaction, and the vapor phase reaction requires specific equipment [44][45][46].…”
Section: Introductionmentioning
confidence: 65%
“…Compared with the previously reported methods which mainly referred to physically filling the dynamic nanopores or chemically bonding to the hydroxyl groups, the strategy proposed in this study is a dual modification method, that is, the use of maleic anhydride (MAn) to improve wood durability (i.e., dimensional stability and decay resistance) via dynamic nanopore filling combined with hydroxyl group elimination. Although acetic anhydride, melamine formaldehyde, sorbitol, and N-methylol melamine have been reported to modify the cell wall for durability improvement in a similar strategy to our work, several drawbacks like the strong acid catalysts employed or formaldehyde release adversely affect their properties and the environment, and thus limit their practical applications [39][40][41][42][43]. Although maleic anhydride was reported to bulk the cell wall and chemically bond to the hydroxyl group, the employed methods still use solvents like DMSO, which are difficult to remove after the reaction, and the vapor phase reaction requires specific equipment [44][45][46].…”
Section: Introductionmentioning
confidence: 65%
“…In addition to si161579, the siRNAs derived from MuLnc1 have also been predicted to target many protein-coding genes with different functions. Therefore, as a precursor of these siRNAs, the lncRNA MuLnc1 may be involved in the response to multiple biotic and abiotic stresses [91].…”
Section: Lncrnas Are Involved In Post-transcriptional Regulationmentioning
confidence: 99%
“…Among these, trans-acting small interfering RNAs (tasiRNAs) or phased secondary small interfering RNAs (phasiRNAs) are two endogenous classes of siRNAs [ 85 , 86 ]. Recently, various studies on lncRNA-derived siRNA havce been reported; among these, the miR390- TAS3 -ARF pathway [ 87 ], the miR3954-lncRNA-phasiRNA-NAC pathway [ 88 ], the mul-miR3954- MuLnc1 -si161579- MuCML27 [ 89 ], and miR2118- PMS1T -phasiRNAs [ 90 ] are well known in various plant species. For instance, a novel lncRNA, MuLnc1 , was targeted by miR3954 to produce 21 nt phasiRNAs in mulberries.…”
Section: Classification Of Lncrnasmentioning
confidence: 99%